2021
DOI: 10.3389/fcell.2021.784421
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Immune Cells CARrying a New Weapon Against Cancer

Abstract: Chimeric antigen receptor (CAR) engineering for T cells and natural killer cells (NK) are now under clinical evaluation for the treatment of hematologic cancers. Although encouraging clinical results have been reported for hematologic diseases, pre-clinical studies in solid tumors have failed to prove the same effectiveness. Thus, there is a growing interest of the scientific community to find other immune cell candidate to express CAR for the treatment of solid tumors and other diseases. Mononuclear phagocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 192 publications
(249 reference statements)
0
5
0
Order By: Relevance
“…Clinical studies that use allogeneic anti-CD7 CAR-T have shown promising results, indicating it as an effective “bridge-to-transplant” strategy for patients with available hematopoietic cell donors. Novel approaches such as the use of other immune cells, like NK and myeloid cells equipped with a CAR as “off-the-shelf” products are being studied, as well as the modification of donor derived T cells through gene editing techniques ( 107 ). With the rapid evolving knowledge of PTCL molecular and pathogenic properties, we will be able to develop efficient and personalized therapies for the treatment of these hard-to-treat diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies that use allogeneic anti-CD7 CAR-T have shown promising results, indicating it as an effective “bridge-to-transplant” strategy for patients with available hematopoietic cell donors. Novel approaches such as the use of other immune cells, like NK and myeloid cells equipped with a CAR as “off-the-shelf” products are being studied, as well as the modification of donor derived T cells through gene editing techniques ( 107 ). With the rapid evolving knowledge of PTCL molecular and pathogenic properties, we will be able to develop efficient and personalized therapies for the treatment of these hard-to-treat diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tools such as TREM2 inhibitors to eliminate immunosuppressive macrophages selectively seeks to restore regular immune responses and stifle tumor growth [ 165 ]. The technique of loading CAR-Mac involves the use of genetically modified CAR-Mac to specifically target tumor cells, thereby augmenting the power and precision of anti-tumor immune responses [ 166 ]. The tactic of inducing macrophage reprogramming, such as with CLEVER-1 inhibitors, recalibrates TAMs from a pro-tumor to an anti-tumor phenotype [ 162 , 167 ].…”
Section: Targeting Heterogeneous Tam Metabolism: Therapeutic Potentia...mentioning
confidence: 99%
“…Cells expressing the chimeric TCR exhibited the idiotype of Sp6 anti-TNP antibody and enabled a non-MHC-restricted response to the hapten TNP. With the evolution of biotechnology, the prototypical design of CAR genes and vectors has gone through several improvements, such as addition of costimulatory domains for better intracellular signaling, bispecific receptors that target more than one antigen, endogenous production of interleukins, immune checkpoint antagonists to enhance CAR-T cell activity, and, more recently, engineering of other immune cells such as natural killer cells, macrophages, and γδ T cells to express the CAR molecule [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%